2020
DOI: 10.1093/eurheartj/ehaa055
|View full text |Cite
|
Sign up to set email alerts
|

Integrated management of atrial fibrillation in primary care: results of the ALL-IN cluster randomized trial

Abstract: Aims To evaluate whether integrated care for atrial fibrillation (AF) can be safely orchestrated in primary care. Methods and results The ALL-IN trial was a cluster randomized, open-label, pragmatic non-inferiority trial performed in primary care practices in the Netherlands. We randomized 26 practices: 15 to the integrated care intervention and 11 to usual care. The integrated care intervention consisted of (i) quarterly AF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
2
35
0
1
Order By: Relevance
“…In the present study, treatment in CS was associated with a 0.15-fold risk for the primary outcome, 0.09-fold risk for thromboembolic events, 0.15-fold risk for relevant bleeding events, 0.17-fold risk for all-cause mortality and a 0.39-fold risk for hospitalizations compared with RMC during follow-up. These benefits were similar to results reported for integrated care versus primary care in other settings, like atrial fibrillation [ 39 ]. We previously reported significantly improved clinical outcomes for the whole thrombEVAL study sample, comprising all patients with various indications of OAC treatment [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, treatment in CS was associated with a 0.15-fold risk for the primary outcome, 0.09-fold risk for thromboembolic events, 0.15-fold risk for relevant bleeding events, 0.17-fold risk for all-cause mortality and a 0.39-fold risk for hospitalizations compared with RMC during follow-up. These benefits were similar to results reported for integrated care versus primary care in other settings, like atrial fibrillation [ 39 ]. We previously reported significantly improved clinical outcomes for the whole thrombEVAL study sample, comprising all patients with various indications of OAC treatment [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, an integrated care apporach in the present mAFA II trial long term extension cohort reduced the risk for rehospitalisation by 31%. Other nurse-driven (or nurse-led) integrated care approachs have also been demonstrated to be clinically beneficial for atrial fibrillation patients [19] , [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“… 33 NVAF can lead to heart failure and vice versa. 35 Recent data showed that integrated care, 36 such as ABC pathway (A = Avoid stroke with anticoagulation, B = better symptom management, and C = Cardiovascular and comorbidity risk management), should be encouraged to reduce the cardiovascular risk of patients with NVAF. 37 Due to the increased risk of clinical outcomes with increasing age, many treatment and preventative strategies should be mentioned.…”
Section: Discussionmentioning
confidence: 99%